2019
DOI: 10.1002/ange.201901224
|View full text |Cite
|
Sign up to set email alerts
|

Highly Crystalline Mesoporous Phosphotungstic Acid: A High‐Performance Electrode Material for Energy‐Storage Applications

Abstract: Heteropoly acids (HPAs) are unique materials with interesting properties, including high acidity and proton conductivity. However, their low specific surface area and high solubility in polar solvents make them unattractive for catalytic or energy applications. This obstacle can be overcome by creating nanoporosity within the HPA. We synthesized mesoporous phosphotungstic acid (mPTA) with a spherical morphology through the self‐assembly of phosphotungstic acid (PTA) with a polymeric surfactant as stabilized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Moreover, the compactness and the distribution of mPTA-Si in the PVA matrix increases and more uniform (white dots are the mPTA-Si particles) with the increases of loading content (Figure 1b-e) It is suggested that the structural order of mPTA in PEM matrix was improved with the increases amount of mPTA [11], owing to the higher particles number (red circle) of fillers. In addition, the surface of the membranes also was found in smooth and no aggregation formed in the structure.…”
Section: Surfacementioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the compactness and the distribution of mPTA-Si in the PVA matrix increases and more uniform (white dots are the mPTA-Si particles) with the increases of loading content (Figure 1b-e) It is suggested that the structural order of mPTA in PEM matrix was improved with the increases amount of mPTA [11], owing to the higher particles number (red circle) of fillers. In addition, the surface of the membranes also was found in smooth and no aggregation formed in the structure.…”
Section: Surfacementioning
confidence: 95%
“…PTA is primarily used as a homogeneous catalyst for acid and oxidation, due to its high acidity and good oxidizing ability. Because the high oxidation level of 6 tungsten in PTA, reducing W 6+ to W 3+ in PTA may produce high energy and power densities for energy cells [11]. In addition, PTA also have been used in fuel cell applications to improve proton conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ilbeygi et al. applied K 3 PW 12 O 40 to the anode material of LIBs and investigated its lithiation mechanism by analyzing the in‐situ X‐ray absorption spectroscopic during cycling test [19] . With the increase of cycling time, the anions of the K 3 PW 12 O 40 , [PW 6+ 12 O 40 ] 3− , are gradually reduced to a completely stabilized structure, [PW 4+ 12 O 40 ] 27− , and the valence state of W hardly ever changes after the 10 th cycle, indicating that the non‐Faradaic Li + storage contributes most of the capacity of K 3 PW 12 O 40 .…”
Section: Application Of Poms In Electrode Materials For Secondary Bat...mentioning
confidence: 99%